FRI0435 INFLUENCE OF BASELINE DEMOGRAPHICS AND DISEASE CHARACTERISTICS ON EFFICACY OF AN ORAL, SELECTIVE TYK2 INHIBITOR, BMS-986165, IN PATIENTS WITH PLAQUE PSORIASIS IN A PHASE 2 TRIAL. (June 2019) - Gordon, Kenneth; Papp, Kim; Gooderham, Melinda; Thaçi, Diamant; Foley, Peter; Morita, Akimichi; Kundu, Sudeep; Kisa, Renata; Napoli, Andrew; Banerjee, Subhashis
Abstract : Background: BMS-986165 is an oral, selective inhibitor of tyrosine kinase 2 (TYK2), an enzyme that activates signal transducer and activator of transcription (STAT)-dependent cytokine signalling pathways involved in the pathophysiology of psoriasis (PsO). In a 12-week, Phase 2 trial of BMS-986165 in patients with moderate to severe plaque PsO, including those with baseline (BL) musculoskeletal symptoms, Psoriasis Area and Severity Index (PASI) 75 responses (primary endpoint) were highest at doses ≥3 mg twice daily (BID; 67–75%) vs placebo (7%; P <0.001), with a favourable safety profile. 1 Objectives: To evaluate the influence of BL demographics (weight, body mass index, age) and disease characteristics (age of onset, presence of musculoskeletal symptoms, disease duration, previous biologic use, PASI score, static Physician Global Assessment [sPGA] score, Dermatology Life Quality Index [DLQI] score) on Week 12 efficacy for the 3 most effective doses of BMS-986165 (3 mg BID, 6 mg BID, and 12 mg once daily [QD]) in the trial. Methods: Adults with moderate to severe plaque PsO (body surface area [BSA] ≥10%, PASI score ≥12, sPGA score ≥3) were randomised equally to 1 of 5 oral doses of BMS-986165 (3 mg every other day, 3 mg QD, 3 mg BID, 6 mg BID, 12 mg QD) or placebo for 12 weeks. Results: A total of 267 patients were treated; subgroup analyses based on BL characteristics are reported for patients treated with the most effective doses of BMS-986165 (≥3 mg BID; n=134). BMS-986165 showed no meaningful differences in efficacy among almost all of the 3 subgroups, including age of onset, presence of musculoskeletal symptoms, and disease duration (Table), with some variability across subgroups. Small patient numbers may underlie observed fluctuations in results. Similar consistency in responses was seen regardless of BL age (18–<45 years, n=66; ≥45 years, n=68), weight (<90 kg, n=81; ≥90kg, n=53), PASI score (<20, n=96 vs ≥20, n=38), DLQI score (<10, n=52; 10–<20, n=62; ≥20, n=20), sPGA score (<4, n=89; ≥4, n=44), and BSA (<20, n=73; ≥20, n=61). Conclusion: In patients with moderate to severe plaque PsO, BMS-986165 demonstrated consistent efficacy at doses ≥3 mg BID regardless of many BL characteristics, including presence of musculoskeletal symptoms, that may impact results. These observations will be evaluated further in ongoing Phase 3 studies (POETYK PSO Phase 3 programme; ClinicalTrials.gov identifiers: NCT03611751 and NCT03624127 ). References: [1] Papp K, et al. N Engl J Med2018;379:1313–1321. Acknowledgement: Editorial/medical writing: Michele Springer and Nicole Draghi, Caudex; funding: Bristol–Myers Squibb Disclosure of Interests: Kenneth Gordon Grant/research support from: Investigator/Grants: AbbVie, Bristol-Myers Squibb, Celgene, Janssen, Eli Lilly, Novartis, Consultant for: Consultant/Honoraria: AbbVie, Almirall, Amgen, Bristol-Myers Squibb, Celgene, Dermavant, Dermira, Janssen, Kyowa Hakko Kirin, Leo Pharma, Eli Lilly, Novartis, Pfizer, Ortho Dermatologics, Sun Pharma, UCB, Kim Papp Grant/research support from: AbbVie, Akros, Allergan, Amgen, Anacor, Arcutis, Astellas, Baxalta, Boehringer Ingelheim, Bristol-Myers Squibb, Can-Fite, Celgene, Coherus, Dermira, Dow Pharma, Eli Lilly, Galderma, Genentech, Gilead, GlaxoSmithKline, InflaRx GmbH, Janssen, Kyowa Hakko Kirin, Leo, MedImmune, Merck (MSD), Merck Serono, Moberg Pharma, Novartis, Pfizer, PRCL Research, Regeneron, Roche, Sanofi-Aventis/Genzyme, Takeda, UCB, Valeant/Bausch Health, Consultant for: AbbVie, Akros, Amgen, Arcutis, Astellas, AstraZeneca, Baxalta, Baxter, Boehringer Ingelheim, Bristol-Myers Squibb, Can-Fite, Celgene, Coherus, Dermira, Dow Pharma, Eli Lilly, Forward Pharma, Galderma, Genentech, Janssen, Kyowa Hakko Kirin, Leo, Meiji Seika Pharma, Merck (MSD), Merck Serono, Mitsubishi Pharma, Novartis, Pfizer, PRCL Research, Regeneron, Roche, Sanofi-Aventis/Genzyme, Takeda, UCB, Valeant/Bausch Health; honoraria: AbbVie, Akros, Amgen, Baxter, Boehringer Ingelheim, Celgene, Coherus, Eli Lilly, Forward Pharma, Galderma, Janssen, Kyowa Hakko Kirin, Merck (MSD), Merck Serono, Mitsubishi Pharma, Novartis, Pfizer, PRCL Research, Sanofi-Aventis/Genzyme, Takeda, UCB, Valeant/Bausch Health; steering committee: AbbVie, Amgen, Boehringer Ingelheim, Celgene, Eli Lilly, Janssen, Kyowa Hakko Kirin, Merck (MSD), Merck Serono, Novartis, Pfizer, Regeneron, Sanofi-Aventis/Genzyme, Valeant/Bausch Health; advisory boards: AbbVie, Amgen, Astellas, Baxter, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, Dow Pharma, Eli Lilly, Galderma, Janssen, Merck (MSD) Novartis, Pfizer, Regeneron, Sanofi-Aventis/Genzyme, UCB, Valeant/Bausch Health, Speakers bureau: AbbVie, Amgen, Astellas, Celgene, Eli Lilly, Galderma, Janssen, Kyowa Hakko Kirin, Leo, Merck (MSD), Novartis, Pfizer, Sanofi-Aventis/Genzyme, Valeant/Bausch Health; scientific officer: Akros, Anacor, Kyowa Hakko Kirin, Melinda Gooderham Grant/research support from: Principal Investigator: AbbVie, Akros Pharma, AMGEN, Arcutis, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, Dermira, Eli Lilly, Galderma SA, GlaxoSmithKline, Glenmark, Janssen, LEO Pharma, MedImmune, Merck, Novartis, Pfizer, Regeneron, Roche, Sanofi Genzyme, UCB, Valeant, Consultant for: Advisory Board: AbbVie, Actelion Pharmaceuticals, AMGEN, Boehringer Ingelheim, Celgene, Eli Lilly, Galderma SA, GlaxoSmithKline, Glenmark, Janssen, LEO Pharma, MedImmune, Merck, Novartis, Pfizer, Regeneron, Roche, Sanofi Genzyme, UCB, Valeant; Consultant: Akros Pharma Inc., AMGEN Inc., Boehringer Ingelheim International GmbH, Celgene Corporation, Eli Lilly and Company, Janssen Inc., Novartis Pharmaceuticals, Sanofi Genzyme, Valeant Pharmaceuticals Inc., Speakers bureau: Speaker: AbbVie Inc., Actelion, AMGEN Inc., Arcutis, Boehringer Ingelheim, Celgene, Eli Lilly, Galderma SA, Glenmark, Janssen, LEO Pharma, Novartis, Pfizer, Regeneron, Sanofi Genzyme, Valeant, Diamant Thaçi Grant/research support from: AbbVie, Almirall, Amgen, Bio Skin, Biogen-Idec, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, Chugai, Dermira, Dignity, Eli Lilly, Forward Pharma, GlaxoSmithKline, Janssen Cilag, Leo Pharma, Novartis, Pfizer, Regeneron, Roche, Sandoz-Hexal, Sanofi, and UCB, Consultant for: AbbVie, Almirall, Bristol-Myers Squibb, Celgene, Dignity, Galapagos, Leo Pharma, Lilly, Novartis, Pfizer, and UCB; honoraria: AbbVie, Almirall, Amgen, Bio Skin, Celgene, Dignity, Janssen, Leo Pharma, Merck Sharp & Dohme, Novartis, Pfizer, Roche-Posay, Sandoz-Hexal, Sanofi, and USB; advisory board: AbbVie, Bio Skin, Bristol-Myers Squibb, Celgene, Dignity, Eli Lilly, Galapagos, GlaxoSmithKline, Janssen Cilag, Leo Pharma, Morphosis, Novartis, Pfizer, Sandoz, Sanofi, and UCB, Peter Foley Grant/research support from: Research Grants: AbbVie, Amgen, Celgene, Janssen, Eli Lilly, Merck, Novartis, Pfizer, Sun Pharma, Galderma: Investigator (clinical trials): AbbVie, Amgen, Boehringer Ingelheim, Celgene, Janssen, Eli Lilly, Merck, Novartis, Pfizer, Sun Pharma, UCB, Valeant, Bristol-Myers Squibb, Celtaxsys, CSL, Cutanea, Dermira, Galderma, Genentech, GlaxoSmithKline, Leo Pharma, Regeneron, Roche, Sanofi; travel grants: Abbvie, Janssen, Lilly, Merck, Novartis, Pfizer, Sun Pharma, Galderma, Leo Pharma, Roche, Sanofi, Consultant for: Advisory Board: AbbVie, Amgen, Celgene, Janssen, Eli Lilly, Merck, Novartis, Pfizer, Sun Pharma, UCB, Valeant, Galderma, GlaxoSmithKline, Leo Pharma, Sanofi; Consultant: Janssen, Eli Lilly, Novartis, Pfizer, UCB Pharma, Bristol Myers Squibb, Galderma, Leo Pharma, Roche, Speakers bureau: Speakers Bureaus/Honoraria: AbbVie, Celgene, Janssen, Lilly, Merck, Novartis, Pfizer, UCB Pharma, Valeant, Galderma, GlaxoSmithKline, Leo Pharma, Roche; Travel Grants: AbbVie, Janssen, Eli Lilly, Merck, Novartis, Pfizer, Sun Pharma, Galderma, Leo Pharma, Roche, Sanofi, Akimichi Morita Grant/research support from: AbbVie GK, Eisai Co., Ltd., Eli Lilly Japan K.K., Kyowa Hakko Kirin Co., Ltd., LEO Pharma KK, Maruho Co., Ltd., Mitsubishi Tanabe Pharma Corporation, Novartis Pharma K.K., and Torii Pharmaceutical Co., Ltd., Consultant for: AbbVie GK, Boehringer Ingelheim Japan, Inc., Celgene K.K., Eli Lilly Japan K.K., Janssen Pharmaceutical K.K., Kyowa Hakko Kirin Co., Ltd., Maruho Co., Ltd., Nichi-Iko Pharmaceutical Co., Ltd., Nippon Kayaku Co., Ltd., Novartis Pharma K.K., and Sun Pharmaceutical Industries Ltd., Speakers bureau: AbbVie GK, Boehringer Ingelheim Japan, Inc., Celgene K.K., Eisai Co., Ltd., Eli Lilly Japan K.K., Janssen Pharmaceutical K.K., Kyowa Hakko Kirin Co., Ltd., Maruho Co., Ltd., Mitsubishi Tanabe Pharma Corporation, Nichi-Iko Pharmaceutical Co., Ltd., Nippon Kayaku Co., Ltd., Novartis Pharma K.K., Sun Pharmaceutical Industries Ltd., Taiho Pharmaceutical Co., Ltd., Torii Pharmaceutical Co., Ltd, and Ushio INC., Sudeep Kundu Shareholder of: Bristol-Myers Squibb, Merck, Employee of: Bristol-Myers Squibb, Renata Kisa Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Andrew Napoli Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Subhashis Banerjee Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb